2018
DOI: 10.1177/0021998318808358
|View full text |Cite
|
Sign up to set email alerts
|

Depth sensing indentation of magnesium/boron nitride nanocomposites

Abstract: Magnesium nanocomposites, considered as energy-saving lightweight materials of future, are a fairly new family of composite materials with enhanced specific strength and ductility compared to pure magnesium and/or magnesium alloys. In the present study, time-dependent plastic deformation of novel light-weight magnesium/boron nitride nanocomposites containing 0.5, 1.5 and 2.5 vol% of nano-boron nitride particulates is studied through a depth-sensing indentation approach against monolithic pure magnesium. The sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…A similar effect can be observed in BN, with BN nanotubes promoting osteogenic differentiation in vitro, and implants coated with BN had enhanced bone fracture healing in mouse models [37,38]. It has also been previously demonstrated that Mg nanocomposites fabricated with low BN percentages using powder metallurgy demonstrated high levels of grain refinement, and enhanced localized recrystallization compared with pure Mg [39][40][41]. As a result of the expected microstructural characteristics of Mg-BN nanocomposites imparted via BN addition to Mg, we hypothesize that Mg-BN nanocomposites will have the improved mechanical properties and increased corrosion resistance needed for orthopedic implant applications.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…A similar effect can be observed in BN, with BN nanotubes promoting osteogenic differentiation in vitro, and implants coated with BN had enhanced bone fracture healing in mouse models [37,38]. It has also been previously demonstrated that Mg nanocomposites fabricated with low BN percentages using powder metallurgy demonstrated high levels of grain refinement, and enhanced localized recrystallization compared with pure Mg [39][40][41]. As a result of the expected microstructural characteristics of Mg-BN nanocomposites imparted via BN addition to Mg, we hypothesize that Mg-BN nanocomposites will have the improved mechanical properties and increased corrosion resistance needed for orthopedic implant applications.…”
Section: Introductionsupporting
confidence: 54%
“…BN nanoparticles, 50 nm in diameter, were incorporated in Mg powder to synthesize BN-Mg nanocomposites of Mg-0.5%BN and Mg-1.5%BN vol.% through powder metallurgy and microwave-assisted rapid sintering methods [39,42]. Mg powder with >98.5% purity and 60-300 µm particle size (Merck, Darm-stadt, Germany) was used as the base metal.…”
Section: Synthesis Of Mg-bn Nanocompositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Haghshenas et al 31 investigated the effects of volume fraction of reinforcement on the depth sensing nanohardness behavior of Mg/BN nanocomposites. They concluded that hardness of the nanocomposites increases with increasing volume fraction of the reinforcement and decreasing activation volume beneath the indenter.…”
Section: Micro and Nano-hardness Propertiesmentioning
confidence: 99%